Elite and amateur orienteers` running biomechanics on three surfaces at three speeds - Herbert-Losier, K.; Mourot, L.; Holmberg, H. C. (Medicine & Science in Sports & Exercise, 2015)
Purpose: Orienteering athletes must adapt to running on various surfaces, with biomechanics likely contributing to performance. Here, our aims were to identify the effect of athletic status and of surface on the running biomechanics of orienteers.